One in ten ever-married women who visited health facilities for various reasons have pelvic organ prolapse in Harari regional state, Eastern Ethiopia - Dawit Abebe; Mohammed Abdurke Kure; Enku Afework Demssie; Sinetibeb Mesfin; Melake Demena; Merga Dheresa (BMC, 2022)
Abstract Background Pelvic organ prolapse remains a neglected public health problem in developing countries. The burden of pelvic organ prolapse varies by region and ranges from 9 to 20%. It poses an impact on women's quality of life and affects their role at the community and family level. Although it has negative consequences and extensive burden, the true feature of pelvic organ prolapse is not well known among ever-married women attending health facilities for various reasons in the study area. Therefore, this study was aimed to assess the magnitude of pelvic organ prolapse and associated factors among ever-married women attending health care services in public Hospitals, Eastern Ethiopia. Methods A facility-based cross-sectional study design was conducted from March 4th to April 5th, 2020 among 458 ever-married women attending public Hospitals in Harar town, Eastern Ethiopia. The study subjects were selected through systematic sampling. The data were collected using a structured questionnaire through face-to-face interviews. Data were analyzed using SPSS version 22 (IBM SPSS Statistics, 2013). The prevalence was reported by proportion and summary measures. Predictors were assessed using a multivariable logistic regression analysis model and reported using an adjusted odds ratio with 95% CI. Statistical significance was declared at p-value < 0.05. Result Of 458 women enrolled in the study, 10.5% of them had pelvic organ prolapse based on women's reporting of symptoms. History of lifting heavy objects [AOR = 3.22, 95% CI (1.56, 6.67)], history of chronic cough [AOR = 2.51, 95% CI (1.18, 5.31)], maternal age of greater than or equal to 55 years [AOR = 3.51, 95% CI (1.04, 11.76)], history chronic constipation (AOR = 3.77, 95% CI (1.54, 9.22) and no history of contraceptive utilization [AOR = 2.41, 95% CI (1.13, 5.05)] were significantly associated with pelvic organ prolapse. Conclusion In this study, one in ten ever-married women who visited health facilities for various reasons have pelvic organ prolapse. Modifiable and non-modifiable risk factors were identified. This result provides a clue to give due consideration to primary and secondary prevention through various techniques.